Desenho de uma poiesis: comunicação de um processo coletivo de criação na arquitetura - Cardoso, Daniel Ribeiro (2008)
Drawing of the poiesis: communication of a collective process of creation in architecture is assigned as a domain of the visuality research. As a work related to scientific visualization, it can be compared to the investigations on representation and communication through visual graphic images. The purpose of this thesis is to reflect on issues concerning the processes of generation and the adequate way to represent them. The process of the form development tipology in architecture is adopted as the object of the research. As a proper object of a culture, the type is perceived as an element that serves as a general principle of creation, a supraindividual mechanism needed for the construction of meaning and identity of a society. In that sense, the houses, instantiation of the same logic of creation, are ways that express a collective intelligence. Given the necessary scale for the perception of its evolution, the object was found in the architecture formed between 1890 and 1980, in the region of Cajuais and Mutamba, southern coast of Ceará. In that context, there are some issues concerning the problematic of the thesis to be considered: How to preserve the processes of generation of cultural object? How to apprehend something that is by its nature operative and informative? Moreover, how to represent adequately a poiesis? The answers to these questions are the hypothesis crux of the thesis that considers the grammar of the form development most appropriate sign to represent for the representation of a poiesis. The articulated theories to support the development of the research are distinct. However, the composed network is in a common area in a environment where theoreticians settle the issues of sign and meaning according to the thinking of Charles S Peirce. The theoretical foundation is based on three views: the new General Theory of Systems as defined by Bunge and Vieira, in which it seeks concepts and methodologies adjusting them to the second view; the Genetic Criticism as proposed by Salles that searches general principles of the creation processes; and Semiotic as a basis for the issues of representation and communication processes. Furthermore, it will be considered authors like Chomsky, Prusinkiewics, Stiny, Duarte, among others that point out the grammar as a representation of process in semiotics systems. Finally, it is proposed a sign poiesis appropriate to a system generator of forms that operates with the evolutionary logic found in the object. Therefore, the result of the research is not only a tool that speculates the generation and the visualization of future forms, but it is also a path for the development of Genetic Criticism